Green Accounting Disclosure and Its Effect on Financial Performance of Mining Company - Destiana, Rizka; Simorangkir, Bella Rizky Anggraini (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
This research examines the influence of environmental costs, environmental performance, and environmental disclosure on financial performance in the mining industry. The population in this study comprises all mining companies listed on the Indonesia Stock Exchange during the period 2018-2022. By using a purposive sampling method, 15 companies meet the criteria with a total of 175 data sets. Quantitative data analysis was employed in this study using time-series data. Data collection method utilized in this research was a documentation method. The analytical tool in this study is the multiple regression analysis. In this study, data is processed by using the SPSS program. The primary contribution of this research is to underscore the importance of effective environmental management within the context of the mining industry. The research findings indicate that environmental costs have a negative influence on financial performance, while environmental performance and environmental disclosure have a positive influence on financial performance.